Ochrona tajemnic w polskim porządku prawnym — tajemnica radcowska i adwokacka - Jabłoński, Mariusz; Węgrzyn, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Professional secrecy, e.g. secrecy of attorneys and secrecy of solicitors also known as the attorney-client privilege is of particular interest to both doctrine and practice. Due to the fact that the issue in question causes controversy, especially when it comes to exceptions to the obligation of professional secrecy, the authors express their doubts whether the provisions on professional secrecy of attorneys and solicitors in the Polish law should be mandatory in absolute terms. On the basis of the law as well as the views expressed in both the doctrine and jurisprudence the Authors justify the answer to the thesis indicated above.
Keywords: polski system prawny; ochrona informacji niejawnych; tajemnica zawodowa; adwokaci; radcy prawni